1977
DOI: 10.1007/bf00385985
|View full text |Cite
|
Sign up to set email alerts
|

Messenger ribonucleoprotein particles in dry wheat and rye embryos

Abstract: Extracts prepared from dry wheat (Triticum aestivum L.; var. Cama) and rye (Secale cereale L.; var. Celestijner) embryos exhibit relatively high endogenous messenger activities in an in vitro protein synthesizing system: up to 400 pmol leucine are incorporated per 50 μl reaction mixture; the messenger/ribosome ratio is estimated at about 0.03. Sucrose gradient analysis of the incubation mixture during cellfree protein synthesis shows a progressive in vitro polysome formation with the native endogenous mRNPs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The paired somatic. heart somatic *cot (b) monosomes and small polysomes (fractions [5][6][7][8][9], and (c) large polysomes (fractions [10][11][12][13][14][15][16][17][18][19][20][21][22] were used for northern blot analysis against probes for the major 1 Figure 5 show the synthesis of proteins from polysomal mRNAs and those in the mRNP fraction extracted from the transition stages of developing somatic and zygotic embryos, i.e. when the patterns of storage protein synthesis change (Fig.…”
Section: Analysis Of Cell-free Translational Products Of Polysomal Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The paired somatic. heart somatic *cot (b) monosomes and small polysomes (fractions [5][6][7][8][9], and (c) large polysomes (fractions [10][11][12][13][14][15][16][17][18][19][20][21][22] were used for northern blot analysis against probes for the major 1 Figure 5 show the synthesis of proteins from polysomal mRNAs and those in the mRNP fraction extracted from the transition stages of developing somatic and zygotic embryos, i.e. when the patterns of storage protein synthesis change (Fig.…”
Section: Analysis Of Cell-free Translational Products Of Polysomal Anmentioning
confidence: 99%
“…Stagespecific activation of different mRNA species is also common during early embryogenic development in the surf clam (22). The presence and importance of mRNPs in plants has not been subjected to intensive study, although there is ample evidence for the presence of 'stored' mRNAs in RNPs in the mature dry seed (10,18,20,24). Their presence during embryogenesis is uncertain, although it has been reported that the mRNA for the ,B subunit of 13-conglycinin increases several days before the accumulation of the protein (14).…”
mentioning
confidence: 99%
“…The germinating wheat embryo has been shown to contain native messenger ribonucleoprotein particles (Peumans and Carlier 1977) having a half-life of 2 h at an optimal germination temperature (Caers et al 1979). Lesions appearing in embryos of reduced vigour may be concerned with those factors which affect the stability of the messenger ribonucleoprotein complex in the celis of the germinating embryo or those factors controlling the rate of turnover of polyA* RNA species in the embryo.…”
Section: Pulsementioning
confidence: 99%
“…Since rye embryos proved to be a useful material for the study of preformed mRNPs (PEUMANS & CARLIER, 1977;PEUMANS et al, 1978), we followed the synthesis of free mRNPs in embryos from ripening rye grains by sucrose density gradient analysis of both the mRNP distribution pattern and the distribution of newly formed RNPs (labelled in their protein or RNA moiety). These experiments demonstrated that free informosomes ( I ) are present throughout E. coli aspartate carbamoyltransferase (EN 2.…”
Section: Rlkjnion De Louvain-en-woluwementioning
confidence: 99%